Clinical observation of gonadal dysgenesis with surgical correction - V.V. Bila; N.M. Kolesnyk; V.H. Zhehulovych; R.M. Yusef; O.S. Zahorodnia (Publishing House TRILIST, 2022)
Anomalies of sexual development, despite their low prevalence, are relevant both due to the rapid expansion of diagnostic capabilities at the genetic and genetic levels, and due to increasing attention to the social adaptation of such patients. This article is devoted to the description of clinical observation of a rare form of sexual rosette anomalies - Swyer syndrome, which consists in the underdevelopment male gonads in persons with 46XY karyotype. The most common and studied cause of male gonadal dysgenesis is a SRY gene mutation, which is responsible for testicular development. So far, several point mutations in genes involved in the development of male gonads have been identified. Genes are located in both autosomes and both sex chromosomes. One of the newest pathogenetic mechanisms of this syndrome is a MYRF gene mutation. The main consequence of this mutation is a violation of myelination, its role in disorders of sex differentiation has recently been shown. Patients with Swyer syndrome at birth have phenotypic traits of the female sex. Delayed sexual development is registered in adolescence; ultrasound reveals a hypoplasia of the uterus, gonads in the form of fibrous bands. Clinical observation of a 27-year-old patient with complaints of lack of menstruation, coarsening of the voice and facial hair growth is present. Examination revealed the female type structure of the external genitalia, clitoral hypertrophy, vaginal aplasia, 46XY genotype, MYRF mutation. Surgery was performed. It included cystoscopy (free urethra, ureteral stenting), laparoscopy (uterus and ovaries in the pelvic cavity are not visualized, gonads are found at the level of the inguinal ring and removed), transperitoneal tunneling of the vagina, dissection of the vertical membrane of the vagina, removal of the clitoris, resection of the labia minora. Patient underwent complete physiological and social adaptation 6 months after operation.